Упростите выражение: (2x-3)^2+(3x-5)(3x+5)+40x Покажите, что значение выражения (2x-3)^2+(3x-5)(3x+5)+40x при x=-2 равно 12.

gelyaangelmat gelyaangelmat    2   15.03.2021 11:45    0

Ответы
Мирималистка Мирималистка  14.04.2021 11:45

-20

Пошаговое объяснение:

(2x-3)^2+(3x-5)(3x+5)+40x = 4x² - 12x + 9 + 9x² - 25 + 40x = 13x² + 28x - 16

при x=-2

13x² + 28x - 16 = 13*(-2)² + 28*(-2) - 16 = 52 - 56 - 16 = -20

ПОКАЗАТЬ ОТВЕТЫ
mczuf mczuf  14.04.2021 11:45

Пошаговое объяснение:

(2x - 3 {)}^{2} + (3x - 5)(3x + 5) + 40x = {4x}^{2} - 12x + 9 + {9x}^{2} - 25 + 40x = {13x}^{2} + 28x - 16

При х=-2

(2x - 3 {)}^{2} + (3x - 5)(3x + 5) + 40x = {4x}^{2} - 12x + 9 + {9x}^{2} - 25 + 40x = {13x}^{2} + 28x - 16 = 52 - 56 - 16 = - 20

Уравнение не ≠ 12

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика